Hypoglycaemia management with a hypercaloric supplementation in neonatal puppies delivered by caesarean section - Fuchs, Kárita da Mata [UNESP]; Pacífico Pereira, Keylla Helena Nobre [UNESP]; de Sousa, Gabriela Carneiro [UNESP]; Xavier, Gleice Mendes [UNESP]; Camargo, Gabriel de Azevedo [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Wiley, 2023)
There is a high perinatal mortality rate in dogs, estimated at 20%, and one of the leading causes of this rate is hypoglycaemia. Therefore, we aimed to evaluate the efficacy of a hypercaloric supplement containing vitamins and amino acids in newborn puppies presenting hypoglycaemia at birth. Ninety-nine pups were divided into four groups: normoglycaemic caesarean section (NORMOCS), hypoglycaemic caesarean section supplemented with the hypercaloric (SUPLCS), hypoglycaemic caesarean section supplemented with glucose (GLICCS) and eutocic delivery (EUT). We evaluated the following parameters glycaemia, Apgar score, neurological reflexes and rectal temperature of neonates at the following moments 5 min (M5), 30 min (M30) and 60 min (M60) after birth. Brachycephalic dogs were 73.3% (22/30) of caesarean sections (c-sections). The puppy's average glycaemia represented about 90% of the maternal glycaemia, while 15.1% (14/99) of the neonates had hypoglycaemia (<90 mg/dL) at M0 and 46.5% (44/99) at M60. Only four neonates had glycaemia below 40 mg/dL at M30 but without showing any clinical signs. The puppy's fasting while waiting for the intraoperative period and the dam's anaesthetic recovery was considered risk factors for hypoglycaemia. There was no difference in mean blood glucose levels or vitality parameters among puppies from the SUPLCS and GLICCS. In conclusion, the hypercaloric supplement can be used as a replacement for glucose in hypoglycaemic puppies and it can also bring nutritional benefits for the puppy. The prepartum glycaemia of the dam is an important parameter to be measured, and the appropriate management of it reduces the chances of the puppies being born with hypoglycaemia.
Keywords: canine; glycaemia; modified Apgar score; neonatology; nutraceuticals